2014
DOI: 10.1039/c3mb70428a
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic analysis of the proteins that are associated with the resistance to paclitaxel in human breast cancer cells

Abstract: Cancers frequently develop resistance to paclitaxel but the underlying molecular mechanisms remain to be determined. We have investigated the proteins that are associated with the paclitaxel resistance in human breast cancer MCF-7 cells using proteomic analysis. Paclitaxel resistant human breast cancer MCF-7 cells (MCF-7/P) were established by escalating the concentrations of paclitaxel to drug-sensitive MCF-7 cells (MCF-7/S). The global protein profiles of MCF-7/P and MCF-7/S were compared using two-dimension… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 42 publications
1
20
0
Order By: Relevance
“…There is strong evidence in the literature of a link between chemoresistance and EMT, which is a critical event in cancer development 22 was also found to be associated with the growth of lung cancer cells 28 . Consistent with these findings, our previous study showed that transgelin 2 was critically involved in the growth of MCF-7/PTX cells 13 transgelin 2 by SAA is likely to be a safer approach for the treatment of breast cancer.…”
Section: Knockdown Of Transgelin 2 Inhibited Paclitaxel Resistance Msupporting
confidence: 80%
See 1 more Smart Citation
“…There is strong evidence in the literature of a link between chemoresistance and EMT, which is a critical event in cancer development 22 was also found to be associated with the growth of lung cancer cells 28 . Consistent with these findings, our previous study showed that transgelin 2 was critically involved in the growth of MCF-7/PTX cells 13 transgelin 2 by SAA is likely to be a safer approach for the treatment of breast cancer.…”
Section: Knockdown Of Transgelin 2 Inhibited Paclitaxel Resistance Msupporting
confidence: 80%
“…Our previous study demonstrated that transgelin 2 was ectopically overexpressed in MCF-7/PTX cells 13 property of MCF-7/PTX cells, attenuated N-cadherin and Vimentin, and increased the expression of E-cadherin ( Fig. 5B and 5C).…”
Section: Knockdown Of Transgelin 2 Inhibited Paclitaxel Resistance Mmentioning
confidence: 77%
“…The PTX-resistant MCF-7 (MCF-7/PTX) cell line was established as previously described. 34 Culture plates and dishes were obtained from Corning Incorporated (Corning, NY, USA). The culture medium was RPMI 1640, supplemented with 10% FBS, 100 mg/mL streptomycin sulfate, and penicillin 100 IU/mL.…”
Section: Materials and Methods Materialsmentioning
confidence: 99%
“…The PTX-resistant MCF-7 (MCF-7/PTX) cell line was established as previously described. 34 Culture plates and dishes were purchased from Corning Incorporated (Corning, NY, USA). Cells were cultured in Roswell Park Memorial Institute (RPMI)-1640 medium, …”
Section: Materials and Methods Materialsmentioning
confidence: 99%